Konstitusi Agraria Upaya Reforma Agraria Melalui Program LARASITA Pensertipikatan Hak Milik Atas Tanah - Nurma Khusna Khanifa (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2016)
One proactive services implemented by BPN in an effort to make it easy for people to land services in obtaininga land certificate program LARASITA (People Services For Land Certificate). BPN services contained within LARASITA in actual field program carried out by the District Land Office or City. LARASITA program is asympathetic effort to serve people whowant to make a land certificate. LARASITA is an innovative policies that depart from the fulfillment of the necessary sense of justice, and is expected to be considered by the public. LARASITA built and developed to make real mandate of Article 33 paragraph (3) of the Constitution of 1945, the Basic Agrarian Law, as well as all laws and regulations in land and keagrariaan. Development LARASITA depart from the will and motivation to bring the Indonesian National Land Agency (BPN RI) with thecommunity, as well as changing the paradigm of implementing the duties and functions of BPN RI waiting oractive or passive to proactive, go to the people directly.